Acute severe asthma in adults. (May 2016) - Bayes, Hannah K.; Thomson, Neil C.
Abstract: Acute severe asthma represents a common medical emergency accounting for >65, 000 UK hospital admissions each year, and asthma still accounts for approximately 1200 UK deaths annually. Risk factors for fatal asthma include poorly controlled disease, inappropriate medical management and adverse behavioural and social factors. Asthma is characterized by chronic airway inflammation, resulting in periodic wheeze, cough and breathlessness. A variety of triggers can cause exacerbations, most commonly viral respiratory tract infections. Exacerbations are identified by an increase in asthma symptoms and fall in lung function. National and international acute asthma management guidelines highlight best practice. All patients presenting with poorly controlled asthma symptoms should be examined and peak expiratory flow (PEF) or forced expiratory volume in 1 second recorded. Patients with PEF <50% of baseline or predicted have a severe exacerbation and should be referred to hospital. Treatment aims to rapidly relieve bronchoconstriction and halt airway inflammation; oxygen, systemic corticosteroids and inhaled bronchodilators are first-line treatments. Patients with features of life-threatening asthma should be given magnesium sulphate and discussed with the intensive care team. Before discharge, medications should be reviewed, a personalized action plan agreed and early follow-up arranged.